2021
DOI: 10.1002/hon.2923
|View full text |Cite
|
Sign up to set email alerts
|

Secondary primary malignancies in patients with multiple myeloma: A single institution experience

Abstract: The purpose of our study is to highlight the demographic characteristics, pathological features, and clinical course of multiple myeloma (MM) patients with secondary primary malignancies (SPM). A retrospective chart review was performed from January 2009 to February 2020. Patients' demographic, pathologic and cytogenetic features, treatment characteristics and clinical outcomes were collected. We identified 871 MM patients including 40 patients who developed SPM. Among the 40 patients with SPM, 17 patients dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The etiology of SPM in MM is likely multifactorial due to host, disease, and treatment-related factors [ 13 ]. Small studies revealed that the specific types of SPM often vary by race and NHWP tend to have more SPM than NHBP [ 14 , 15 ]. Except for one patient, all the patients with SPM in our study underwent at least one transplant, with 5/13 cases of hematological second malignancies developing after anti-MM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of SPM in MM is likely multifactorial due to host, disease, and treatment-related factors [ 13 ]. Small studies revealed that the specific types of SPM often vary by race and NHWP tend to have more SPM than NHBP [ 14 , 15 ]. Except for one patient, all the patients with SPM in our study underwent at least one transplant, with 5/13 cases of hematological second malignancies developing after anti-MM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with those of a previous study. 8 There have been few reports that describe the prognostic comparisons of patients with SPM post-ASCT and the general population. Barth 10 In our study, the OS rate in patients with SPM post-ASCT was compatible with that of primary cancers in the general Japanese population.…”
Section: A B C Dmentioning
confidence: 99%
“…[1][2][3][4] Because patients with MM survive longer, the incidence rate of second primary malignancies (SPM) in long-term survivors of MM is increasing. To date, only a few studies have evaluated SPM in real-world patients, [5][6][7][8][9] particularly in Asian patients with MM. [10][11][12] In this study, we analyzed Japanese patients with MM who underwent ASCT using large registry data.…”
Section: Introductionmentioning
confidence: 99%